Getting to the roots of black-grass: allelopathic interactions for control of Alopecurus myosuroides - Hickman, Darwin T. (2022)
Black-grass is a highly detrimental herbicide-resistant grass weed of arable agriculture in Europe. While cultural controls can partially mitigate black-grass, there remains great need for additional alternative control methods. A potential alternative approach to weed control is to harness the allelopathy (biochemical inhibition) of potent species. Cereals like wheat and rye synthesise and exude from their roots a class of compounds, benzoxazinoids, which have both plant-plant allelopathic potential, and other multi-kingdom inhibitory effects. Petri dish assays of benzoxazinoid compounds with documented allelopathic potential identified 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one (DIMBOA) and 2,4-dihydroxy-1,4-benzoxazin-3-one (DIBOA) as promising compounds in inhibiting root development in black-grass populations, with inhibition unrelated to variability in herbicide resistance profile. Wheat is highly tolerant of these compounds, indicating species-specificity in their allelopathic potential. Crude cereal root exudates collected in hydroponic and axenic sand systems were also examined for allelopathic potential. Therein, wheat and rye exudates were confirmed as inhibitory, while a wider range of inhibitory potential was found in exudates of ancestor wheats. Subsequent chemical analyses of these exudates tentatively identified a suite of benzoxazinoid compounds present, with those related to DIMBOA exuded from modern wheat, and those related to DIBOA exuded from rye and ancestor wheats. Selection for DIMBOA synthesis may thus be an unintended consequence of wheat domestication. 2-hydroxy-1,4-benzoxazin-3-one (HBOA) was noted as another potential allelochemical, which was examined and confirmed as a potent black-grass inhibitor. Crude cereal exudates were capable of allelopathy towards black-grass in soil, but benzoxazinoids degraded quickly in many soils, reducing their inhibitory potential. This explains the greater efficacy of biological crop treatments exuding allelochemicals towards black-grass, in comparison to synthetic chemical treatments when applied in combination in glasshouse assays. Further dose-response analyses of the more persistent DIBOA-related compound 4-hydroxy-1,4 benzoxazin-3-one(D-DIBOA) identified that it is not an effective black-grass inhibitor, indicating that another allelochemical must be identified for the development of a pure bioherbicide. Therefore, it is concluded that an allelopathic crop is a more realistic application of benzoxazinoid inhibitors for black-grass control, in combination with effective deployment of cultural control methods.